2015 2nd International Conference on Electrical Information and Communication Technologies (EICT) 2015
DOI: 10.1109/eict.2015.7391991
|View full text |Cite
|
Sign up to set email alerts
|

Study of the variation of resistivity, permeability and curie temperature of rare earth metal Yttrium (Y) substitution on Ni0.60Zn0.40−xYxFe2O4 (x=0.05, 0.10, 0.15) ferrites

Abstract: In this research work, ferrites with compositions of Ni 0.60 Zn 0.40-x Re x Fe 2 O 4 where x=0.05, 0.10, 0.15 were prepared by double sintering ceramic technique. The samples were pre sintered at 10000 C for 4 hours in air and sintered at 1250 0 C for 3 hours. The influence of Yttrium (Y) substitution on various properties of Ni-Zn ferrites have been studied in this work. Investigations were carried out by the measurements of AC resistivity, Permeability and Curie temperature of the sample. AC resistivity show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This increased the resistivity of prepared samples when compared with Dy-0. It has been found in the literature that sometimes resistivity may be reduced by introducing the rare-earth ions [39]. In such case, the Dy 3+…”
Section: Main Textmentioning
confidence: 99%
“…This increased the resistivity of prepared samples when compared with Dy-0. It has been found in the literature that sometimes resistivity may be reduced by introducing the rare-earth ions [39]. In such case, the Dy 3+…”
Section: Main Textmentioning
confidence: 99%
“…It is observed that an increase in the amount of Eu (x = 0.15) content result in an increase in the coverage of the grains by the EuFeO3 phase and this is beneficial to grain growth. Figure 3 shows, the imaginary component µ'' first rises slowly and then increases quite abruptly making a peak at a certain frequency where the real component µ' is falling sharply [17]. This feature is well known as the ferromagnetic resonance [21].…”
mentioning
confidence: 97%
“…Many researchers reported the structural, magnetic and electrical properties of Ni-Zn ferrites of different combinations in bulk [12][13][14][15][16][17][18] forms.…”
Section: Introductionmentioning
confidence: 99%